Application of Chelex-100 and SPR-IDA Resin in Combination with the Optimized Beam Deflection Spectrometry for High-Sensitivity Determination of Iron Species in Sediment Porewater - Hanna Budasheva; Mohanachandran Nair Sindhu Swapna; Arne Bratkič; Dorota Korte (Sensors, 2025)
In this work, photothermal beam deflection spectrometry (BDS), combined with a passive sampling technique of diffusive gradients in thin film (DGT), is optimized to improve the method’s sensitivity. The limit of detection (LOD) is then reduced by a factor of 2 (to the value of 20 nM). The functionality of the technique is compared for Chelex-100 (Ch-100) and suspended particulate reagent–iminodiacetate resin (SPR-IDA), used as binding resins in passive samplers. The absorption capacity of SPR-IDA resin is found to be less than 1 μM and far below that one of Chelex-100 resin (around 6 μM). The BDS technique is applied for determination of iron redox species concentration in sediment porewater. It is found that Fe in sediment porewater occurs both in Fe2+ (0.073 μM) and Fe3+ (0.095 μM) forms. The validation of the presented method reveals that the BDS technique ensures good repeatability, reproducibility, and reliability.